If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * 6 + 86 = x * 10 + -6 Reorder the terms for easier multiplication: 6x + 86 = x * 10 + -6 Reorder the terms: 86 + 6x = x * 10 + -6 Reorder the terms for easier multiplication: 86 + 6x = 10x + -6 Reorder the terms: 86 + 6x = -6 + 10x Solving 86 + 6x = -6 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 86 + 6x + -10x = -6 + 10x + -10x Combine like terms: 6x + -10x = -4x 86 + -4x = -6 + 10x + -10x Combine like terms: 10x + -10x = 0 86 + -4x = -6 + 0 86 + -4x = -6 Add '-86' to each side of the equation. 86 + -86 + -4x = -6 + -86 Combine like terms: 86 + -86 = 0 0 + -4x = -6 + -86 -4x = -6 + -86 Combine like terms: -6 + -86 = -92 -4x = -92 Divide each side by '-4'. x = 23 Simplifying x = 23
| f(x)=9xsquared+5x+1 | | 2[x+8]=-4[5x-2]+8x | | 2x-7+4x+15=56 | | (4x-7)+(-12-8x)= | | 3+25x=20x+12 | | 15-4t=4 | | 3+25x=20x-12 | | e^4x=10 | | 2z(z)+20z=0 | | 3+25x=2-0x+12 | | 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 |